2019
DOI: 10.1111/pce.13512
|View full text |Cite
|
Sign up to set email alerts
|

Functional relationships between hydraulic traits and the timing of diurnal depression of photosynthesis

Abstract: The hydraulic coordination along the water transport pathway helps trees provide adequate water supply to the canopy, ensuring that water deficits are minimized and that stomata remain open for CO 2 uptake. We evaluated the stem and leaf hydraulic coordination and the linkages between hydraulic traits and the timing of diurnal depression of photosynthesis across seven evergreen tree species in the southern Andes. There was a positive correlation between stem hydraulic conductivity (k s ) and leaf hydraulic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…One possible reason is that K leaf and P50 leaf are influenced by both xylem [12,25] and outside-xylem pathways [6,9,26], thus obscuring such a trade-off. Conversely, other studies have found a significant leaf hydraulic trade-off in Mediterranean-type forest [27] and across angiosperm species from different biomes [5]. Therefore, a global meta-analysis incorporating a broad range of plant functional groups and water environments would provide a more complete understanding of such a trade-off [28].…”
Section: Introductionmentioning
confidence: 95%
“…One possible reason is that K leaf and P50 leaf are influenced by both xylem [12,25] and outside-xylem pathways [6,9,26], thus obscuring such a trade-off. Conversely, other studies have found a significant leaf hydraulic trade-off in Mediterranean-type forest [27] and across angiosperm species from different biomes [5]. Therefore, a global meta-analysis incorporating a broad range of plant functional groups and water environments would provide a more complete understanding of such a trade-off [28].…”
Section: Introductionmentioning
confidence: 95%
“…This can explain why the height and DBH of the initial seedlings of the species increase 3-5 times merely in 3 years' plantation (from the year of 2016 to 2019). Higher photosynthetic rates also result in higher leaf anatomy traits (Oguchi et al, 2003;He et al, 2017;Hua et al, 2017), stomatal traits (McAusland et al, 2016Lawson and Vialet-Chabrand, 2019), transpiration rate and leaf hydraulic conductivity (Maherali et al, 2008;Bucci et al, 2019). Indeed, we found that these traits for the eight fast-growing species were three to five times greater than for native species.…”
Section: Table 2 |mentioning
confidence: 49%
“…High photosynthetic rates can result in increased stomatal conductance (Lawson & Vialet-Chabrand, 2019; McAusland et al., 2016) and transpiration rates (Bucci et al., 2019; Maherali et al., 2008; Santos et al., 2018). L. leucocephala has evolved leaf traits for maximizing photosynthetic capacity and increasing overall growth, which plausibly facilitates it to outperform the native dominant plant species.…”
Section: Discussionmentioning
confidence: 99%